Self-Control and Emotional Maturity Reduce Consumptive Behavior in Women - Lestari, Aprillia Citra Dewi Suci; Paryontri, Ramon Ananda (Universitas Muhammadiyah Sidoarjo, 2024)
Abstract: This research investigates the relationship between self-control and emotional maturity with consumptive behavior among women in Sumorame Village, Indonesia. General Background: Globalization has increased consumptive behavior, particularly among women reliant on branded goods and online shopping. Specific Background: Previous studies show significant levels of consumptive behavior among women, but few focus on rural communities like Sumorame. Knowledge Gap: This study addresses this gap by analyzing the impact of self-control and emotional maturity on consumptive behavior. Aims: The objective is to determine how these psychological factors influence purchasing tendencies. Results: A sample of 301 women revealed a significant negative correlation (rx1y = -0.368, p < 0.05; rx2y = -0.527, p < 0.05), indicating that higher self-control and emotional maturity lead to reduced consumptive behavior. Novelty: This research enhances understanding of economic behavior in rural contexts. Implications: Findings highlight the need for educational programs to improve self-control and emotional maturity, promoting better financial practices among women in Sumorame Village. Highlights: Higher self-control correlates with lower consumptive behavior in women. Emotional maturity significantly influences purchasing tendencies among women. Educational programs can enhance self-control and emotional maturity to improve financial practices. Keywords: Self-Control, Emotional Maturity, Consumptive Behavior, Women